Risk Factors for Hemoptysis in Ethiopia: A Hospital Based and Case-Control Study - Ingbar, Corey (Sriwijaya Journal of Internal Medicine, 2024)
Introduction: Hemoptysis, the expectoration of blood from the lower respiratory tract, is a prevalent symptom with diverse etiologies. While global data on risk factors exists, information specific to the Ethiopian context is limited. This study aimed to identify risk factors associated with hemoptysis in Ethiopia. Methods: A hospital-based case-control study was conducted at three tertiary hospitals in Addis Ababa, Ethiopia, from January 2022 to December 2022. Cases were patients aged ≥18 years presenting with hemoptysis. Controls were age- and sex-matched individuals attending the same hospitals for non-respiratory conditions. Data were collected using a structured questionnaire and medical record review. Logistic regression was used to identify independent risk factors. Results: A total of 400 participants (200 cases and 200 controls) were included. The mean age was 42.5 years (SD ± 15.2). Independent risk factors for hemoptysis included: previous history of tuberculosis (adjusted odds ratio [AOR] = 4.8, 95% CI 2.9-7.9), current smoking (AOR = 3.2, 95% CI 1.8-5.7), biomass fuel exposure (AOR = 2.5, 95% CI 1.4-4.5), and history of chronic obstructive pulmonary disease (COPD) (AOR = 2.1, 95% CI 1.2-3.7). HIV infection was not independently associated with hemoptysis in this study (AOR = 1.3, 95% CI 0.7-2.4). Conclusion: This study identified previous tuberculosis, smoking, biomass fuel exposure, and COPD as independent risk factors for hemoptysis in Ethiopia. These findings highlight the need for targeted public health interventions, including smoking cessation programs, improved indoor air quality, and early detection and management of tuberculosis and COPD, to reduce the burden of hemoptysis in Ethiopia.